2005
DOI: 10.1088/0953-2048/18/4/024
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of melt-assisted growth in Bi-2223 tapes utilizing rapid heating rates

Abstract: Recent differential thermal analysis studies on green Bi-2223 tapes showed two phase transitions, with onset temperatures 800 and 820 °C. From microstructural examination of the long-term phase formation in the tapes the higher temperature endotherm was associated with a partial melt. In this study it is demonstrated how control of the heating rate can promote the partial melt (characterized by DTA), and thereby improve the transport current, Ic. XRD, SEM and transport measurements in field show microstructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Higher temperatures form more liquid, so rearrangement and densification can occur but secondary phase formation can result. The ability to control the melt to some degree as regards better superconductor transport properties is shown in a separate publication [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher temperatures form more liquid, so rearrangement and densification can occur but secondary phase formation can result. The ability to control the melt to some degree as regards better superconductor transport properties is shown in a separate publication [7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in this study has demonstrated a reduction in secondary phases which is thought to be due to an enhancement of the volume of liquid phase [6,7]. The focus of this work is on making a link between the transients in the initial stages of reaction and the secondary phase formation after prolonged heat treatment.…”
Section: Introductionmentioning
confidence: 88%